Mindfulness: jak oswoić lęk językowy studentów języków obcych i zachęcić ich do uważnego życia? - Blachowska-Szmigiel, Marzena (Acta Neophilologica, 2021)
This article focuses on the possibilities of employing mindfulness in order to support a foreign language student in developing the competence to deal with language anxiety and to strengthen a sense of psychological well-being in the face of the contra-dictory challenges of modern times. First, the author describes the difficult situation of a contemporary student of foreign languages who functions in two axiologically contradictory realities: fluid modernity and crystallized university reality. Then the issue of language anxiety is discussed, and finally the author presents the concepts of the mindfulness program in foreign philology.